Hematoxylin, an Alternative Substrate of Tyrosinase - Crous, Chantalle; Swart, Ivanke A.; Pretorius, Judey; van der Kooy, Frank; Petzer, Jacobus P.; Petzer, Anél (Planta Medica, 2024)
Mushroom tyrosinase from Agaricus bisporus (abTYR) is often used during the development of tyrosinase inhibitors for medicinal and cosmetic purposes. In the search for novel tyrosinase inhibitors, this study identified hematoxylin as an alternative substrate for abTYR. The interaction of hematoxylin with abTYR was investigated through spectrophotometric and chromatographic analyses. The results showed that hematoxylin acted as an abTYR substrate and exhibited Michaelis–Menten kinetic behaviour at concentrations below 1.25 mM. The substrate properties of hematoxylin were similar to the natural tyrosinase substrate, L-3,4-dihydroxyphenylalanine (L-DOPA), with regards to Km, while Vmax was eightfold lower. The main oxidation product formed during the reaction of abTYR with hematoxylin was identified as hematein. This is the first report of the interaction of hematoxylin with abTYR.
Keywords: Agaricus bisporus; tyrosinase; hematoxylin; tyrosinase inhibitor